2022
DOI: 10.3390/vaccines10020175
|View full text |Cite
|
Sign up to set email alerts
|

Tipping the Fencesitters—The Impact of a Minimal Intervention Enhanced with Biological Facts on Swiss Student Teachers’ Perception of HPV Vaccination Safety

Abstract: Not much is known about the role of scientific knowledge in vaccination decision making. This study is based on previous findings that the concern about the human papillomavirus (HPV) agent mutating back to a virulent HPV was common among Swiss student teachers and turned out to be one factor of vaccine hesitancy. The study investigate the impact of a standard public health brochure describing the effectiveness, safety, and importance of HPV vaccination on young student teachers, and the additional effect of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…This measure, adopted from previous research [ 58 , 59 , 60 ], was a composite of agreement scores with the following four statements: People who do not get vaccinated risk becoming very sick Vaccines are effective in preventing diseases I can get sick from vaccines I am concerned that there may be something I do not know about in vaccines …”
Section: Methodsmentioning
confidence: 99%
“…This measure, adopted from previous research [ 58 , 59 , 60 ], was a composite of agreement scores with the following four statements: People who do not get vaccinated risk becoming very sick Vaccines are effective in preventing diseases I can get sick from vaccines I am concerned that there may be something I do not know about in vaccines …”
Section: Methodsmentioning
confidence: 99%
“…In 2004, Keselman and colleagues demonstrated that scientific knowledge could help to identify what they called HIV myths-scientifically wrong beliefs that students firmly articulated before they learned more conceptual scientific knowledge about HIV and AIDS [20]. In the years to come, S|E|H studies investigated students' scientific knowledge in various fields, for example about HPV (Human Papilloma Virus) vaccination [21,22], about menopause and cardiovascular diseases in females [23], about epilepsy and people suffering from this disease [24], and about viruses and antibiotics [25].…”
Section: Concern 2: the Role Of Knowledge In S|e|hmentioning
confidence: 99%
“…Another important point is that while health is increasingly considered a key topic in science education [14,20,22], the role of medicine education within science education still goes widely unnoticed [23,24]. This is the case even though, in the classroom, science education could strongly benefit from embracing the wide range of topics regarding noncommunicable and communicable diseases (e.g., cancer, allergies, vaccination [24,25]). While contemporary health education is focused on well-being and health promotion [14], medicine education aims to teach future citizens to become informed patients in contexts of shared decision-making [26].…”
Section: Theoretical Background 21 a Look Back: Teaching About Health...mentioning
confidence: 99%